PERAN SEKTOR PERTANIAN DI PROVINSI JAWA TIMUR PADA SEBELUM DAN SETELAH PEMBERLAKUAN OTONOMI DAERAH - Gilang Wirakusuma; Hani Perwitasari; Irham Irham (Universitas Wahid Hasyim, 2015)
This study aims to know agricultural sector/sub sector which have a role as leading sector/sub sector in East Java Province, trend of contribution of agricultural sector for GDRP and employment in East Java, determinant factor of agricultural sector growth. Parameters of this study goals are divided in two periode, those periode are before Local Autonomy era and during Local Autonomy era. Analysis tools that used for this study are Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share Analysis, and Linear Trend.Before Local Autonomy era, crop plant is the leading sub sector for East Java Province. Animal husbandry is the leading sub sector for East Java in Local Autonomy era. This study show that national economic activity is the most dominant factor for agricultural sector growth before Local Autonomy era and during Local Autonomy era. Trend of contribution of agricultural sector in employment and GDRP show the declining line. Declining agricultural sector contribution in GDRP faster than it's contribution in employment.Keywords: Determinant factor of growth, local autonomy, role of agricultural sector.